2007
DOI: 10.1007/s11096-007-9155-6
|View full text |Cite
|
Sign up to set email alerts
|

Description of pharmacist interventions during physician–pharmacist co-management of hypertension

Abstract: Pharmacist recommendations for alterations in drug therapy generally occurred early in the course of the study and were largely to intensify therapy through higher dosages or additional medications. Pharmacist-physician co-management of BP is effective at reducing BP and improving BP control rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
86
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 44 publications
7
86
2
1
Order By: Relevance
“…The vast majority of changes occurred in the first 2 months of the intervention and dose titrations usually occurred every 2 to 4 weeks. 12 Thus, our study clearly demonstrated that high BP control rates, including in patients with diabetes, can be achieved without FDCs.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…The vast majority of changes occurred in the first 2 months of the intervention and dose titrations usually occurred every 2 to 4 weeks. 12 Thus, our study clearly demonstrated that high BP control rates, including in patients with diabetes, can be achieved without FDCs.…”
supporting
confidence: 56%
“…14 The 2 most effective strategies that were used in our Collaborative Management of Hypertension study 11 for patients with previously uncontrolled hypertension was to switch to chlorthalidone or add low-dose spironolactone even in patients already taking a CCB plus an ACEI or ARB. 12 The need for such add-on therapy greatly limits the presumed simplicity of the FDC.…”
Section: Could Fdcs Lead To Irrational Choices or Switching?mentioning
confidence: 99%
“…This rate was similar to rates seen in programs where pharmacists were not integrated into the prescriber teams 16,27,28 and was much lower than rates documented in other settings, where the pharmacist was part of the prescriberbased team. 6,29,30 If this service were to become permanent, a concentrated effort to engage prescribers from the beginning would be crucial. Trust is a significant component of functional, collaborative working relationships, but without time and repeated interactions, trust between physicians and pharmacists cannot develop.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that pharmacists are well suited to provide support, able to create effective relationships with providers and achieve high provider acceptance of pharmacist recommendations [24,25]. Furthermore, pharmacists have successful providers in patient-centered medical homes [26] and have provided care with demonstrated improved patient outcomes [27][28][29].…”
mentioning
confidence: 99%